2009
DOI: 10.3177/jnsv.55.346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant- and Fish-Oil Derived n-3 Polyunsaturated Fatty Acids on Counteraction of n-3 Fatty Acid Shortage in Adult Rats Fed a Lard Diet

Abstract: Summary These studies aimed to compare the effects of ␣ -linolenic acid (ALA) ϩ eicosapentaenoic acid (EPA) ϩ docosahexaenoic acid (DHA) on plasma-lipid concentrations and preferential fat intake of rats fed a lard diet (LD). Each of 2 groups of 4-wk-old male rats was used in studies 1 and 2. In studies 1 and 2, two groups of rats received the LD (LD group) and the fish-oil diet (FD; FD group), and the LD and the perilla-oil diet (PD; PD group), respectively (dietary treatment period). After 6 wk, 6 rats per g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Many reports showed that diets enriched with fish-oil containing n-3 polyunsaturated FAs reduce blood lipid concentration (16,(27)(28)(29). In this study, although consumption of the FD in rats fed the ZnD diet was lower than that in rats fed the ZnA diet, the plasma and liver lipid concentration of the ZnD rats was significantly lower than that of the ZnA rats.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Many reports showed that diets enriched with fish-oil containing n-3 polyunsaturated FAs reduce blood lipid concentration (16,(27)(28)(29). In this study, although consumption of the FD in rats fed the ZnD diet was lower than that in rats fed the ZnA diet, the plasma and liver lipid concentration of the ZnD rats was significantly lower than that of the ZnA rats.…”
Section: Discussionmentioning
confidence: 39%
“…We reported previously that when rats that had been fed either the LD or the FD for 6 wk were placed on a self-selection regimen of both diets, both groups of rats counteracted the shortage of FAs at the beginning of the self-selection period and consumed the LD and the FD to maintain n-6 FAs/n-3 FAsϭ2.7 (16). From these results, we assumed that rats had the ability to self-select lipids in an adequate essential FA ratio spontaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fish-oil HFD guarded against the overeating of fats ( 10 ). Although fish-oil is nutritionally less desirable than lard and soybean-oil, when rats were placed on a self-selection regimen of a lard diet and a fish-oil diet they had the ability to consume both diets to obtain an adequate ratio of essential fatty acids ( 11,12 ). We also reported that the lard HFD had food properties preferable to those of the LFD because energy density (kcal/g) of the HFD is higher than that of the LFD ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, adults in the United States consume about 35% of their total daily fat from saturated fat and 20% from polyunsaturated fat [27, 28], although the recommended intake is closer to 30% and 40%, respectively [29]. Although there are relatively few studies in animals, the evidence that exists shows that chronic consumption of diets high in saturated fatty acids, such as those containing lard, compared to those high in unsaturated fatty acids, such as those with fish oil, can promote hyperphagia and weight gain while raising TG levels, even when these diets contain similar concentrations of overall fat [30, 31]. To understand possible mechanisms that underlie these disturbances, the present study examined under both acute and chronic conditions the behavioral, physiological and neurochemical effects of a diet containing relatively high levels of saturated fatty acids (HiSat), as compared to one containing higher levels of unsaturated fatty acids (USat).…”
Section: Introductionmentioning
confidence: 99%